THE ROLE OF TECHNOLOGY TO SOLVE LANGUAGE LEARNING PROBLEMS: A PRACTICAL CASE OF COMMON CORE SCIENTIFIC STUDENTS - Fakhr-Eddine, I.; Aitdaoud, Mohammed (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2019)
The misspellings are among the most important reasons that distort the Arabic language. It is based on the letters that are added or deleted, the words that separates or connects, the Humazat